Structures and mechanisms for synthetic DNA motors - Haley, NEC (2017)
DNA provides an ideal substrate for nanoscale construction and programmable dynamic mechanisms. DNA mechanisms can be used to produce DNA motors which do mechanical work, e.g. transportation of a substrate along a track. I explore a method for control of a DNA mechanism ubiquitous in DNA motor designs, toehold-mediated strand displacement, by which one strand in a duplex can be swapped for another. My method uses a mismatch between a pair of nucleotides in the duplex, which is repaired by displacement. I find that displacement rate can be fine-tuned by adjusting the position of the mismatch in the duplex, enabling the design of complex kinetic behaviours. A bipedal motor [1, 2] is designed to walk along a single-stranded DNA track. Previously the motor has only taken a single step, due to a lack of designs to extend the single-stranded track. I present a novel design for track held under tension using a 3D DNA origami tightrope, and verify its assembly. The bipedal motor design is adapted and a method to specifically place motors on tightropes is demonstrated. Motor operation is investigated on truncated tracks and tightrope tracks by electrophoresis and spectrofluorometry. The motor does not accumulate appreciably at the track end; this is tentatively attributed to rearrangement of the motor between track sites without interaction with fuel. Tightrope origami can hold single-stranded DNA under pN tension. I use tightropes to study hybridization kinetics under tension and find dramatic, non-monotonic changes in hybridization rate constants and dissociation constants with tension in the range ∼0-15 pN. Extended tracks for a 'burnt-bridges' motor which destroys its track as it moves [3] are created on the inside of DNA nanotubes, which can be polymerised to create tracks up to a few mm in length, and on tiles which I attempt to join in a specific order. Crossing of the motor between tubes is verified, and microscopy experiments provide some evidence that track is being cleaved by the motor, a requirement for movement along the track. Tile based tracks are imaged by super-resolution DNA PAINT [4], providing proof-of-principle for track observation to infer motor movement.